8th International Conference on Mushroom Biology and Mushroom Products held in New Delhi (19-22 November 2014) - A Report - Kamal, Shwet; Singh, Manjit (Mushroom Research, 2015)
The 8th International Conference on Mushroom Biology and Mushroom Products (ICMBMP) was hosted in the historic city of Delhi, India at the National Agricultural Science Centre Complex from 19-22 November 2014. The conference, with 70 participants from 26 countries from outside India, including about 150 scientists, 40 entrepreneurs, 30 farmers and 20 students from India, was held for four days with multifarious activities ranging from oral presentations, poster presentations, exhibitions, scientists-farmer interaction, a field visit, and networking. The 8th International Conference on Mushroom Biology and Mushroom Products included one theme lecture, 13 keynote addresses, 63 oral and 128 poster presentations covering diverse topics such as mushroom diversity, genetics, biochemistry, biology & development, medicinal aspects, value addition, economics of mushroom production, etc. The topics were divided into ten sessions.